PENDIDIKAN ISLAM PERIODE KHULAFAUR RASYIDIN (Abu Bakar, Umar bin Khottab, Utsman bin Affan, Ali bin Abi Thalib - Laeli Tri Agustina (Universitas Ahmad Dahlan, 2019)
After the Prophet Muhammad SAW. died, the Ansar wanted the people who succeeded to be the Caliphs from among them. Ali bin Abi Talib wanted him to be the Caliph, for he was the son-in-law and close relative of the Prophet. But most of the Muslims want Abu Bakr. Then he became the Caliph. The people who had been doubters, immediately took ba'iah to Abu Bakr. Then the Caliphate continued by Umar bin Khottab, Uthman ibn Affan, and the last Caliph of Ali bin Abi Tahalib. The caliphs focused on education, religious awareness, and the solidity of the Islamic State. The educational material exemplified by the Prophet. is tawhid education, prayer education (worship), education adab polite in family and in social (social life), education personality and education of defense and security. It can be a reference for predicting and becoming a reference for better education in the future